PENGKAJIAN PROGRAM LEMBAGA KURSUS DAN PELATIHAN (LKP) DALAM MENYELENGGARAKAN PROGRAM PENDIDIKAN KECAKAPAN HIDUP (PKH) DI SUMATERA UTARA - Julaga Situmorang (Universitas Negeri Medan, 2012)
This study is aimed to find out as well as to describe the readiness of Training and Cources Institution (LKP) in conducting life skills education programme in North Sumatera,those are including (1) programme management, (2) learning process, (3) suitable material and curriculum developments, (4) learning methods and media had been conducted, (5) trainingprogramme and achievement assessment, (6) programme affectivity, and (7) program outcomes into graduate and works place. The population in this study are those are Training and Cources Institutions thats are take part in Lifeskills Educations Program (PKH) under the Directorate of Development Training and Course (PAUDNI) in North Sumatera 2010, they are 51 LKP. The sellected LPK have got social fund from PAUDNI. There are 29 LKP (57%) are sellected as sample, those are proportionally taken from all PKH that are run by the LKP in the region. Thestudy is conducted qualitative and quantitatively. The data is obtained from the Head of LKP, instructor, participants, and the documents by using questionaires, observation, interview, anddocumentation technique. The data were analyzed by both qualitative and quantitative analysis and presented as percentage, and qualitative description.The results showed that in general the PHK-LKP programme have been conducted well in most of the institution. However, in some institution the programme is not maintained in good order to master them in their competencies such as personal, social, and accademic competencies. It could be seen from the developedcurriculum, syllabus, lesson plann, and teaching materials were not fully contains the personal, social, and accademic competencies. Eventhough the learning methods and media had been varied, however the problem solving method and ICT interactive media that are important to build life skill to overcome life problems and self strugling have not achieved. Based on mastery learning criteria that is set by the PAUDNI on PKH programme, it is known that the affectivity of lifs kills has not been achieved. The national evaluation have been used to measure vocational competency, however the programme evaluation has not been measured comprehensively (context, input, proccess, and product). It is found that the educationprogramme have reach 68%, that is assigned to be lower that the criteria for successful indicator given by the Directorate of Development Training and Course guiding (72%), including forthose self working. Therefore, it is suggested that all bodies such as BP-PPNFI, UPT, and others, to empower LKP staff to develop the curriculum and instructional material that suitableto reach personal, social, and academic competencies. It is also suggested to conduct trace study in order to expose the impact of life skill education programme by gathering information fromthe user.